Deconstruction of basic accounting principles through the values of sufism in the Syarah Ḥikam by Sheikh Aḥmad Zarrūq - Raden Arfan Rifqiawan; Abdul Ghofur; Ali Murtadho; Ratno Agriyanto; Warno Warno (Universitas Islam Negeri Walisongo Semarang, 2024)
Purpose - The purpose of this study is to deconstruct the basic principles of accounting, which are often viewed as overly materialistic, by integrating seven Sufi values from the Syarah Ḥikam by Sheikh Aḥmad Zarrūq. This research seeks to create a more balanced accounting paradigm integrating financial gains with moral, social, and spiritual responsibilities.Method - This research utilizes a literature review method with a Derridean deconstruction approach, combining the text of Syarah Ḥikam with accounting literature. The deconstruction process involves identifying the material-spiritual binary to explore the integration of Sufi values into accounting principles.Result - The study's results show that integrating Sufi values strengthens the moral and justice aspects of accounting. This creates a more holistic approach that balances financial profit with spiritual and social responsibilities.Implication - This research has implications for the development of a more ethical and sustainable accounting system that balances material gain with moral and spiritual responsibilities relevant to both business and social practices.Originality - This study is unique in its use of classical Sufi texts to deconstruct the basic accounting principles. This novel approach in modern accounting studies has yet to be widely explored. By integrating spiritual values into accounting, this approach is expected to complement and enrich the current accounting perspectives, aiming not merely for fairness but for truth, fostering a better balance between material aspects and moral, social, and spiritual responsibilities.